2005
DOI: 10.1051/0004-6361:20052797
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances in 43 metal-poor stars

Abstract: Abstract.We have derived abundances of O, Na, Mg, Al, Si, Ca, Sc, Ti, V, Cr, Fe, Ni, and Ba for 43 metal-poor field stars in the solar neighbourhood, most of them subgiants or turn-off-point stars with iron abundances [Fe/H] ranging from −0.4 to −3.0. About half of this sample has not been spectroscopically analysed in detail before. Effective temperatures were estimated from uvby photometry, and surface gravities primarily from Hipparcos parallaxes. The analysis is differential relative to the Sun, and was ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 74 publications
(145 reference statements)
11
84
2
Order By: Relevance
“…The Ni/Fe ratio in the neutral gas of I Zw 18 is solar, with [Ni/Fe] = −0.05 ± 0.23. We note that [Ni/Fe] remains essentially null over a wide range of metallicities in nearby stars (also in DLAs; Izotov et al 2001b) while at the same time [α/Fe] increases at low-metallicity (Jonsell et al 2005). This implies that Ni and Fe evolve in parallel, and it is therefore not surprising that we also find a solar ratio in I Zw 18.…”
Section: The Iron Group Elementssupporting
confidence: 54%
See 1 more Smart Citation
“…The Ni/Fe ratio in the neutral gas of I Zw 18 is solar, with [Ni/Fe] = −0.05 ± 0.23. We note that [Ni/Fe] remains essentially null over a wide range of metallicities in nearby stars (also in DLAs; Izotov et al 2001b) while at the same time [α/Fe] increases at low-metallicity (Jonsell et al 2005). This implies that Ni and Fe evolve in parallel, and it is therefore not surprising that we also find a solar ratio in I Zw 18.…”
Section: The Iron Group Elementssupporting
confidence: 54%
“…It is thus likely that the enrichment from SNe Ia, if any, is identical in the H  phase and in the H  phase. This value of [O S /Fe] lies between 0 (solar O/Fe ratio) and the value in Galactic halo stars (Barbuy 1988) and in metal-poor stars in the solar neighborhood (Jonsell et al 2005), suggesting an early enrichment by high-mass stars (see Izotov & Thuan 1999).…”
Section: The Iron Group Elementsmentioning
confidence: 79%
“…Fulbright (2002), for example, found a correlation between the observed space velocities of a relatively small sample of stars (with metallicities in the range −2.0 ≤ [Fe/H] < −1.0) and their [α/Fe]; stars with lower [α/Fe] were argued to be associated with faster space motions. Gratton et al (2003) reported that the stars in their sample with substantial prograde rotation about the Galactic center exhibited higher [α/Fe] than those with small or retrograde rotation, as confirmed later by Jonsell et al (2005). Ishigaki et al (2010) found that in the metallicity range −2 < [Fe/H] < −1, stars on orbits reaching a maximum distance from the Galactic plane |Z| > 5 kpc possess [Mg/Fe] ∼ 0.1 dex lower than those that only reach |Z| < 5 kpc.…”
Section: Introductionmentioning
confidence: 60%
“…Stellar abundance data were compiled from several different studies. For the solar neighbourhood, the data were compiled from several authors (Bensby & Feltzing 2006;Ecuvillon et al 2004;Fabbian et al 2009a;Gratton et al 2000;Gustafsson et al 1999, Jonsell et al 2005, Spite et al 2005, while the Cepheid abundances in Fig. 7 were taken from the works by Andrievski et al (2002aAndrievski et al ( ,b,c, 2004 and Luck et al (2003Luck et al ( , 2006.…”
Section: Abundance Datamentioning
confidence: 99%